IMPACT OF THE STUDENT FACILITATOR AND EXPLAINING MODEL INTEGRATED WITH SOCIO-SCIENTIFIC ISSUES ON ANALYTICAL THINKING SKILLS IN BIOLOGY EDUCATION - Maryanti; Wicaksana, Ervan J; Mursyd, Danial ` (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
The Merdeka Curriculum is designed to transform education by enhancing student engagement and preparing learners to face the complexities of the modern era. However, observations at SMA Negeri 9 revealed that students still struggle to connect information from various sources and show low participation in class discussions. This study aimed to examine the effect of the Student Facilitator and Explaining (SFE) model integrated with Socio-Scientific Issues (SSI) on students’ analytical thinking in biology learning. The research used a quasi-experimental method with a non-randomized control group pretest-posttest design. Samples were selected using purposive sampling, consisting of an experimental class applying the SFE-SSI model and a control class using Problem-Based Learning (PBL). Data were collected through essay tests and observation sheets, and then analyzed using One-Way ANCOVA. The results showed a significant effect of the learning model on analytical thinking [F(1,69) = 12.245, p < 0.001, ηp² = 0.151]. It is concluded that the SFE model integrated with SSI effectively enhances students’ analytical thinking in biology learning.